Oxford Energy Forum, Issue 105 - Bassam Fattouh; Malcolm Keay (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2016)
This issue of Oxford Energy Forum (OEF) looks at the Paris Agreement (which came out of COP21 – the 21st Conference of Parties under the United Nations Framework Convention on Climate Change) along with its implications for individual energy sources, for particular countries and regions, and for specific policy areas. Perhaps most striking is the range of views contained in the articles here and the disparity of impacts as between different sources, countries, and policy areas. Whereas in the last issue of OEF (where the focus was on electricity), there was much emphasis on the fundamental changes the industry is undergoing as a result of the rapid growth of low-carbon sources, and the similarity of the challenges in different parts of the world, the emphasis in this issue is on diversity. While some areas are seeing major changes and challenges, others are continuing with something little different from business-as-usual. The same applies to fuels; electricity is in the front line in most countries in relation to climate change policy, but for the oil and gas industries the challenges seem to be more to do with the medium- to longer-term. Perhaps as a result, investment markets seem distinctly uninterested in either the challenges or the opportunities offered by the low-carbon transition. Is this just realism or dangerous complacency about future developments?
Keywords: 330